THE DESIGN OF SUCCESSION PLANNING BASED ON COMPETENCY AND PERFORMANCE AT PT BUKALAPAK.COM - NABILA PRIATNO, AYASHA
Many cases of vacancy occurred at PT Bukalapak.com, and the longest vacancy was 172 days. So far, PT Bukalapak.com has only relied on external resources to replenish vacant positions. Meanwhile, it takes quite a long time to carry out external recruitment especially the unemployment rate of Indonesian citizens with undergraduate education level and above is relatively low. Therefore, it is necessary to design a succession planning so that the company can identify employees from within the company that have the potential to fill the vacancy. The design of a succession plan in this study was carried out for a critical position in the Customer Satisfaction Management (CSM) Function. The design of a succession planning is carried out through three major stages, namely identification of talent pool, assessment of individual competencies, and determination of the priority of replacement candidates. Identification of the talent pool is carried out with a 4x4 human asset matrix consisting of two components, namely performance and potential. Individual competency assessment is done by measuring the gap of individual competencies against the competency of the intended position. Then, determining the priority of substitute candidates is done using the analytic hierarchy process which involves three criteria, namely competency gap, position level, and tenure with weights of 0.648, 0.270, and 0.082, respectively. Based on the talent pool identification, there are 4 CSM employees in quadrant 1A, 12 CSM employees are in quadrant 1B, 11 CSM employees are in quadrant 1C, 1 CSM employee is in quadrant 2B, and 2 CSM employees are in quadrant 2D. Employees who are further reviewed for competency assessment and determining priority of replacement candidates are employees of quadrant 1A. Of the four employees in quadrant 1A, candidate C had the highest score in the competency gap criteria in almost all competency gap score calculations for ten critical positions except for the assessment of the Head of Service Quality Monitoring and Service Outreach Program Manager. Candidate C was also selected as the first priority for ten critical positions except for the positions of Head of Service Quality Monitoring, Higher Priority Manager, Service Quality Assurance & Quality Control Manager, and Service Outreach Program Manager. That is because candidate C has relatively longer experience compared to other candidates in the field of customer service.